Step 1

\(\displaystyle-{\frac{{{2}{x}}}{{{7}}}}-{\frac{{{x}}}{{{21}}}}-{\frac{{{5}{x}}}{{{42}}}}\) is an expression because it is contains set of terms using the operation.

Step 2

Solve the above expression

\(\displaystyle\Rightarrow-{\frac{{{2}{x}}}{{{7}}}}-{\frac{{{x}}}{{{21}}}}-{\frac{{{5}{x}}}{{{42}}}}\)

\(\displaystyle\Rightarrow{\frac{{-{6}{\left({2}{x}\right)}-{2}{x}-{5}{x}}}{{{42}}}}\)

\(\displaystyle\Rightarrow{\frac{{-{12}{x}-{2}{x}-{5}{x}}}{{{42}}}}\)

\(\displaystyle\Rightarrow-{\frac{{{19}}}{{{42}}}}{x}\)